2006
DOI: 10.1186/1471-2296-7-73
|View full text |Cite
|
Sign up to set email alerts
|

What do family physicians consider an error? A comparison of definitions and physician perception

Abstract: Background: Physicians are being asked to report errors from primary care, but little is known about how they apply the term "error." This study qualitatively assesses the relationship between the variety of error definitions found in the medical literature and physicians' assessments of whether an error occurred in a series of clinical scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 50 publications
(60 reference statements)
1
31
0
5
Order By: Relevance
“…In a survey, 17 definitions were found for error and 14 for ‘adverse event’ [1]. Another review found 24 definitions for error, with a range of opinions as to what constitutes an error [2]. A need was thus identified for a comprehensive classification, populated by concepts with agreed definitions [3, 4], each labelled by ‘preferred terms’.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey, 17 definitions were found for error and 14 for ‘adverse event’ [1]. Another review found 24 definitions for error, with a range of opinions as to what constitutes an error [2]. A need was thus identified for a comprehensive classification, populated by concepts with agreed definitions [3, 4], each labelled by ‘preferred terms’.…”
Section: Introductionmentioning
confidence: 99%
“…Elder et al 38 reviewed the literature for definitions of error. They then devised scenarios representative of preventable problems experienced by family physicians and surveyed family physicians as to whether an error or mistake had occurred according to Reason's definition of error 39.…”
Section: Resultsmentioning
confidence: 99%
“…17 To promote a common understanding and ease the comparison of international datasets from different reporting systems, WHO Patient Safety commissioned work to develop a framework for an International Classification for Patient Safety (ICPS) (figure 2). 18 19…”
Section: Adverse Incident Reportingmentioning
confidence: 99%